Framing the climate-development nexus in the European Union. Issue 4 (3rd July 2016) - De Roeck, Frederik; Delputte, Sarah; Orbie, Jan
Abstract: This paper aims to assess the framing of adaptation in the development discourse of the European Union (EU). Theoretically, three frames (security, growth and justice/equity) are constructed. Overall, we find clear traces of the EU's normative aspirations as a global actor. Instead of framing climate change as a national or global security threat, human security implications of climate change are emphasised, representing it as a threat to individual livelihoods. Justice/equity considerations are also voiced, acknowledging the disproportionate impact of climate change on developing countries. In terms of agency, we find mostly a global, top-down framing of adaptation in developing countries.